Personality factors and profiles in variants of irritable bowel syndrome - Farnam, Alireza (Baishideng Publishing Group Inc, 2007)
AIM: To study the association between irritable bowel syndrome (IBS) variants (constipation, diarrhea, or both) and personality traits in non-psychiatric patients. METHODS: IBS was diagnosed using the Rome II diagnostic criteria after exclusion of organic bowel pathology. The entry of each patient was confirmed following a psychiatric interview. Personality traits and the score of each factor were evaluated using the NEO Five Factor Inventory. RESULTS: One hundred and fifty patients were studied. The mean age (± SD) was 33.4 (± 11.0) year (62% female). Subjects scored higher in neuroticism (26.25 ± 7.80 vs 22.92 ± 9.54, P < 0.0005), openness (26.25 ± 5.22 vs 27.94 ± 4.87, P < 0.0005) and conscientiousness (32.90 ± 7.80 vs 31.62 ± 5.64, P < 0.01) compared to our general population derived from universities of Iran. Our studied population consisted of 71 patients with Diarrhea dominant-IBS, 33 with Constipation dominant-IBS and 46 with Altering type-IBS. Scores of conscientiousness and neuroticism were significantly higher in C-IBS compared to D-IBS and A-IBS (35.79 ± 5.65 vs 31.95 ± 6.80, P = 0.035 and 31.97 ± 9.87, P = 0.043, respectively). Conscientiousness was the highest dimension of personality in each of the variants. Patients with C-IBS had almost similar personality profiles, composed of higher scores for neuroticism and conscientiousness, with low levels of agreeableness, openness and extraversion that were close to those of the general population. CONCLUSION: Differences were observed between IBS patients and the general population, as well as between IBS subtypes, in terms of personality factors. Patients with constipation-predominant IBS showed similar personality profiles. Patients with each subtype of IBS may benefit from psychological interventions, which can be focused considering the characteristics of each subtype.